Estrogen Receptor-Dependent Proteasomal Degradation of the Glucocorticoid Receptor Is Coupled to an Increase in Mdm2 Protein Expression - Kinyamu, H. Karimi (American Society for Microbiology, 2003)
Glucocorticoids and estrogens regulate a number of vital physiological processes. We developed a model breast cancer cell line, MCF-7 M, to examine potential mechanisms by which the ligand-bound estrogen receptor (ER) regulates glucocorticoid receptor (GR)-mediated transcription. MCF-7 cells, which endogenously express ERα, were stably transfected with mouse mammary tumor virus promoter-luciferase (MMTV-LUC) reporter and GR expression constructs. Our results demonstrate that treatment with estrogen agonists (17β-estradiol [E2], diethylstilbestrol, genistein), but not antagonists (tamoxifen or raloxifene), for 48 h inhibits GR-mediated MMTV-LUC transcription and chromatin remodeling. Furthermore, estrogen agonists inhibit glucocorticoid induction of p21 mRNA and protein levels, suggesting that the repressive effect applies to other GR-regulated genes and proteins in MCF-7 cells. Importantly, GR transcriptional activity is compromised because treatment with estrogen agonists down regulates GR protein levels. The protein synthesis inhibitor cycloheximide and the proteasome inhibitor MG132 block E2-mediated decrease in GR protein levels, suggesting that estrogen agonists down regulate the GR via the proteasomal degradation pathway. In support of this, we demonstrate that E2-mediated GR degradation is coupled to an increase in p53 and its key regulator protein Mdm2 (murine double minute 2), an E3 ubiquitin ligase shown to target the GR for degradation. Using the chromatin immunoprecipitation assay, we demonstrate an E2-dependent recruitment of ERα to the Mdm2 promoter, suggesting a role of ER in the regulation of Mdm2 protein expression and hence the enhanced GR degradation in the presence of estrogen agonists. Our study shows that cross talk between the GR and ER involves multiple signaling pathways, indicative of the mechanistic diversity within steroid receptor-regulated transcription.